2019
DOI: 10.1590/0034-7167-2018-0368
|View full text |Cite|
|
Sign up to set email alerts
|

Quality of life related to health for heart failure patients

Abstract: Objective: To assess the quality of life related to health for heart failure patients and to relate sociodemographic and clinical data. Method: It is an observational and transversal study, with quantitative approach, carried out in a heart failure ambulatory in the state of Pernambuco. Results: In the sample (n=101), there was prevalence of men older than 60 years old, married and professionally inactive. The quality of life related to health, based on the Minnesota Living With Heart Failure Questionnaire, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
2
8
0
5
Order By: Relevance
“…Additionally, patients' quality of life significantly related to age that explained the lower quality of life in this study (patients' mean age = 72.74 years) than that in Paz's study (mean age = 60.23 years). 20 Higher quality of life was associated with better clinical outcomes which was reported previously. 39 As a prognosis indicator of readmission and mortality, the concern with the individuals' quality of life has been highlighted in the Health Sciences area.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Additionally, patients' quality of life significantly related to age that explained the lower quality of life in this study (patients' mean age = 72.74 years) than that in Paz's study (mean age = 60.23 years). 20 Higher quality of life was associated with better clinical outcomes which was reported previously. 39 As a prognosis indicator of readmission and mortality, the concern with the individuals' quality of life has been highlighted in the Health Sciences area.…”
Section: Discussionsupporting
confidence: 68%
“…Patients' quality of life in our study was better than that reported in Chen's study (44.4) 38 and worse than that in Paz's study (34.3). 20 Only patients with a reduced ejection fraction (HFrEF) were included in Chen's study and we enrolled patients with reduced ejection fraction (HFrEF), preserved ejection fraction (HFpEF) or mid‐range ejection fraction (HFmrEF) in this study. The reason that worse quality of life in Chen's study may be that when ejection ability of left ventricle decreased, patients' physical symptoms would exacerbate, resulting in poor quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heart failure is a chronic disorder caused by a structural or functional impairment in the ability of the heart ventricle to fill or eject the blood effectively (Paz et al, 2019). The overall prevalence of heart failure raises with age, particularly after the age of 64.…”
Section: Introductionmentioning
confidence: 99%
“…QoL can predict death and hospitalization in individuals with HF [ 10 ], as well as adverse cardiovascular outcomes in CCC patients [ 11 ]. Individuals with CD present lower scores of QoL [ 12 – 19 ] and individuals with CCC present lower QoL when compared to healthy individuals [ 14 ], to those with the indeterminate form of CD [ 12 , 16 ], and to those with HF from other etiologies [ 15 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%